Loop of Streptomyces Feruloyl Esterase Plays an Important Role in the Enzyme's Catalyzing the Release of Ferulic Acid from Biomass - Uraji, Misugi (Appl Environ Microbiol, 2018)
Feruloyl esterases (FAEs) are key enzymes required for the production of ferulic acid from agricultural biomass. Previously, we identified and characterized R18, an FAE from Streptomyces cinnamoneus NBRC 12852, which showed no sequence similarity to the known FAEs. To determine the region involved in its catalytic activity, we constructed chimeric enzymes using R18 and its homolog (TH2-18) from S. cinnamoneus strain TH-2. Although R18 and TH2-18 showed 74% identity in their primary sequences, the recombinant proteins of these two FAEs (recombinant R18 [rR18] and rTH2-18) showed very different specific activities toward ethyl ferulate. By comparing the catalytic activities of the chimeras, a domain comprised of residues 140 to 154 was found to be crucial for the catalytic activity of R18. Furthermore, we analyzed the crystal structure of rR18 at a resolution of 1.5 Å to elucidate the relationship between its activity and its structure. rR18 possessed a typical catalytic triad, consisting of Ser-191, Asp-214, and His-268, which was characteristic of the serine esterase family. By structural analysis, the above-described domain was found to be present in a loop-like structure (the R18 loop), which possessed a disulfide bond conserved in the genus Streptomyces. Moreover, compared to rTH2-18 of its parental strain, the TH2-18 mutant, in which Pro and Gly residues were inserted into the domain responsible for forming the R18 loop, showed markedly high k(cat) values using artificial substrates. We also showed that the FAE activity of TH2-18 toward corn bran, a natural substrate, was improved by the insertion of the Gly and Pro residues. IMPORTANCE Streptomyces species are widely distributed bacteria that are predominantly present in soil and function as decomposers in natural environments. They produce various enzymes, such as carbohydrate hydrolases, esterases, and peptidases, which decompose agricultural biomass. In this study, based on the genetic information on two Streptomyces cinnamoneus strains, we identified novel feruloyl esterases (FAEs) capable of producing ferulic acid from biomass. These two FAEs shared high similarity in their amino acid sequences but did not resemblance any known FAEs. By comparing chimeric proteins and performing crystal structure analysis, we confirmed that a flexible loop was important for the catalytic activity of Streptomyces FAEs. Furthermore, we determined that the catalytic activity of one FAE was improved drastically by inserting only 2 amino acids into its loop-forming domain. Thus, differences in the amino acid sequence of the loop resulted in different catalytic activities. In conclusion, our findings provide a foundation for the development of novel enzymes for industrial use.